Severe growth defect in a Schizosaccharomyces pombe mutant defective in intron lariat degradation. - Nam, K (1997)
The cDNAs and genes encoding the intron lariat-debranching enzyme were isolated from the nematode Caenorhabditis elegans and the fission yeast Schizosaccharomyces pombe based on their homology with the Saccharomyces cerevisiae gene. The cDNAs were shown to be functional in an interspecific complementation experiment; they can complement an S. cerevisiae dbr1 null mutant. About 2.5% of budding yeast S. cerevisiae genes have introns, and the accumulation of excised introns in a dbr1 null mutant has little effect on cell growth. In contrast, many S. pombe genes contain introns, and often multiple introns per gene, so that S. pombe is estimated to contain approximately 40 times as many introns as S. cerevisiae. The S. pombe dbr1 gene was disrupted and shown to be nonessential. Like the S. cerevisiae mutant, the S. pombe null mutant accumulated introns to high levels, indicating that intron lariat debranching represents a rate-limiting step in intron degradation in both species. Unlike the S. cerevisiae mutant, the S. pombe dbr1::leu1+ mutant had a severe growth defect and exhibited an aberrant elongated cell shape in addition to an intron accumulation phenotype. The growth defect of the S. pombe dbr1::leu1+ strain suggests that debranching activity is critical for efficient intron RNA degradation and that blocking this pathway interferes with cell growth.